Analisis Framing Berita Covid-19 di Media Online News - Muharram Fahri; Eceh Trisna Ayuh (JOPPAS: Journal of Public Policy and Administration Silampari, 2022)
The aim of this research is to see how the media framing news about Covid-19 in the online media Okezone.com and Tribunnews.com. This study uses the Robert N. Etman framing analysis method with a descriptive qualitative approach. Data collection techniques by viewing and observing Covid-19 news in the online media Okezone.com and Tribunnews.com. The overall results of the study are based on the Robert N. Etman framing analysis model with 4 aspects, namely Define Problem, Diagnose Causes, Make Moral Judgment, Treatment Recommendation, stating that the prominence of news articles related to Covid-19 on Okezone.com discusses the impact of Covid-19 in several sectors. Meanwhile, Tribunnews.com provides updates on the development of the Covid-19 case. Tribunnews.com also highlights the issue of anticipation by the government regarding the handling of Covid-19 ahead of Christmas and New Year. The conclusion of the research is that Okezone.com news places more emphasis on the issue of articles on the impact of Covid-19 in various ways such as propaganda, celebration of certain days, cases that occur in society, and also focuses on the impact on the education and economic sectors and Tribunnews.com is more on updates on the development of the Covid-19 case, starting from the latest number of cases, the number of positive cases, deaths and also those who have recovered. Keywords: Covid-19, Framing Analysis, Reporting